2015
DOI: 10.1007/s11103-015-0362-6
|View full text |Cite
|
Sign up to set email alerts
|

Virus tolerance and recovery from viral induced-symptoms in plants are associated with transcriptome reprograming

Abstract: Plant recovery from viral infection is characterized by initial severe systemic symptoms which progressively decrease, leading to reduced symptoms or symptomless leaves at the apices. A key feature to plant recovery from invading nucleic acids such as viruses is the degree of the host's initial basal immunity response. We review current links between RNA silencing, recovery and tolerance, and present a model in which, in addition to regulation of resistance (R) and other defence-related genes by RNA silencing,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 62 publications
0
28
0
1
Order By: Relevance
“…Recently, it was reported that CMD-susceptible cassava cultivars that displayed no recovery or showed a weak recovery, accumulate higher levels of viral small interfering RNAs (vsiRNAs) compared with genotypes that exhibited a strong recovery (Bengyella et al, 2015; Patil and Fauquet, 2015a; Kuria et al, 2016; Rogans et al, 2016). While these observations provide the first insights into small RNA (sRNA) profiles of CMD recovered and non-recovered phenotypes, important questions remain.…”
Section: Reversionmentioning
confidence: 99%
“…Recently, it was reported that CMD-susceptible cassava cultivars that displayed no recovery or showed a weak recovery, accumulate higher levels of viral small interfering RNAs (vsiRNAs) compared with genotypes that exhibited a strong recovery (Bengyella et al, 2015; Patil and Fauquet, 2015a; Kuria et al, 2016; Rogans et al, 2016). While these observations provide the first insights into small RNA (sRNA) profiles of CMD recovered and non-recovered phenotypes, important questions remain.…”
Section: Reversionmentioning
confidence: 99%
“…Recovery merupakan peristiwa pemulihan pada tanaman terinfeksi virus. Fenomena recovery dicirikan oleh adanya gejala infeksi awal yang parah, kemudian semakin menurun hingga hilang atau tidak bergejala pada daun yang baru berkembang (Bengyella et al, 2015). Lebih lanjut, Hagen et al (2008) Titer virus pada tiap varietas mentimun yang diuji diestimasi berdasarkan pengukuran nilai absorbansi ELISA (Tabel 2).…”
Section: Infeksi Sqmv Pada Lima Varietas Mentimununclassified
“…In many cases, symptom attenuation can be seen in the upper part of the plant, called recovery (Ghoshal and Sanfaçon, ). The capability for recovery depends on the host plant species/variety–virus interaction (Bengyella et al , ; Paudel and Sanfaçon, ) and is influenced by environmental factors, such as temperature (Fondong et al , ). Recovery is also linked to gene silencing and its dependence on temperature (Szittya et al , ).…”
mentioning
confidence: 99%